Relationship between Conformity and Consumptive Behavior in Female Adolescents - Aghesna Fadhila Rahmatika; Rosita Endang Kusmaryani (Bina Nusantara University, 2020)
The research aimed to investigate the relationship between conformity and consumptive behavior in female adolescents. It applied a quantitative method with ex-post facto design. The sample was 97 female adolescents in Yogyakarta and was determined using a convenience sampling technique. They completed two questionnaires of conformity and consumptive behavior. The instrument validation technique used content validity, and the validity of the instruments was measured by psychology measurement experts. The instruments' reliability was analyzed using Cronbach Alpha with coefficients of 0,914 (consumptive behavior) and 0,790 (conformity). Data analysis techniques used Pearson product-moment correlation analysis. The result of the research shows that there is a significant positive relationship between conformity and consumptive behavior in female adolescents. In other words, conformity can be a strong predictor of consumptive behavior in female adolescents.